Ascorbic Acid Increases the Thrombogenicity of Cellular Matrices - Hindriks, Georg A; Sixma, Jan J; de Groot, Philip G (Thrombosis and Haemostasis, 1991)
We have studied the influence of ascorbate on extracellular matrix formation in cultured human endothelial cells, smooth muscle cells and fibroblasts and measured the influence of the changed composition of their isolated extracellular matrices on their affinity for platelets. When endothelial cells were grown for a week in the presence of ascorbate, no influence on proline incorporation in their extracellular matrix was found. In accordance, no influence on platelet adhesion or aggregate formation on these matrices was detected. When smooth muscle cells were cultured in the presence of ascorbate, a strong increase in the amount of collagen types I and III in the extracellular matrix was found. When these matrices were perfused with whole blood, a significant enhanced increase in aggregate formation was observed. No influence was seen on the total coverage of the matrix with platelets. When fibroblasts were grown in the presence of ascorbate, no significant increase in proline incorporation in their matrix was measured. However, an increased adhesion of platelets was seen to the matrices at lower shear rates. We conclude that ascorbate feeding has a significant effect on endogenous deposited matrices of smooth muscle cells and fibroblasts, and that the changed composition had profound effects on platelet interaction with these matrices.